9 - «Ni meeting, ni défilé» Le syndicalisme de participation en Côte d’Ivoire a-t-il vécu ? by Ismaîla Touré - Ismaîla Touré (Africa Development, 1998)
Following the socio-economic crises, protests and strikes which affected Côte d'Ivoire in 1990, participative trade-unionism was blamed for formenting social unrest The state embarked on series of measures, culminating in the banning of the May day march. In this article, the author castigates the 'single party* regime, the PDCI-RDA, as the absolute master in a so-called multi-party democracy, comparing it to communism in its practice, in an economic context paradoxically dominated by capitalism. Although the founding elements of trade unionism have given way to other realities, the author arrives at the conclusion that participative trade-unionism still exists in Côte d'Ivoire, but to improve its efficiency, such a trade unionism must also be an integrative one.